Flooded pasts : UNESCO, Nubia, and the recolonization of archaeology - Carruthers, William (Cornell scholarship online, 2022)
This book examines a world famous yet critically underexamined event-UNESCO's International Campaign to Save the Monuments of Nubia (1960-80)-to show how the project, its genealogy, and its aftermath not only propelled archaeology into the postwar world but also helped to "recolonise" it. In the book, the author asks how postwar decolonisation took shape and what role a colonial discipline like archaeology - forged in the crucible of imperialism - played as the "new nations" asserted themselves in the face of the global Cold War. As the Aswan High Dam became the centerpiece of Gamal Abdel Nasser's Egyptian revolution, the Nubian campaign sought to salvage and preserve ancient temples and archaeological sites from the new barrage's floodwaters